2017
DOI: 10.1007/s12613-017-1499-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of combustion zone and evolution of mineral phases along bed height in ore sintering

Abstract: Quantitative parameters of bed combustion, including the thickness of the combustion zone (TCZ), the maximum temperature of the combustion zone (MTCZ), and the bed shrinkage, were characterized through a series of sinter pot tests in transparent quartz pots. The results showed that TCZ first ascended and then descended as the sintering process proceeded. The sintering process was divided into four stages according to the variation rate of the TCZ. A "relative-coordinate" method was developed to obtain the actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, when the selfpossessed moisture of limonitic nickel laterite further rises to 26 mass%, the maximum exhaust-gas temperature is dramatically lowered to 208 °C. As confirmed in previous studies [30,31], the decomposition of the abundant crystal water in limonitic nickel laterite during sintering would result in the formation of highly porous sinter, which subsequently leads to rather low heat front velocity. This adversely affects the transformation of the heat supplied by the combustion of anthracite to sinter bed in the high temperature zone and the efficient utilization of hightemperature exhaust-gas in the lower part.…”
Section: Thermodynamic Conditions During Sinteringsupporting
confidence: 74%
“…However, when the selfpossessed moisture of limonitic nickel laterite further rises to 26 mass%, the maximum exhaust-gas temperature is dramatically lowered to 208 °C. As confirmed in previous studies [30,31], the decomposition of the abundant crystal water in limonitic nickel laterite during sintering would result in the formation of highly porous sinter, which subsequently leads to rather low heat front velocity. This adversely affects the transformation of the heat supplied by the combustion of anthracite to sinter bed in the high temperature zone and the efficient utilization of hightemperature exhaust-gas in the lower part.…”
Section: Thermodynamic Conditions During Sinteringsupporting
confidence: 74%
“…Afterward, the exhaust-gas temperature is maintained at a certain level because of the continuous water evaporation. With the further proceeding of sintering process, the exhaust-gas temperature substantially rises to the maximum value due to heat transfer and chemical reaction [44,45]. When sintering is finished, the exhaust-gas temperature is reduced gradually.…”
Section: Thermodynamic and Kinetic Conditions During Sinteringmentioning
confidence: 99%
“…It is well known that the decomposition of extensive crystal water of limonite ores such as limonitic nickel laterite during sintering leads to the formation of high porous sinter and then rather low heat front velocity [44][45][46]. Thus, the heat generated by the combustion of anthracite cannot be effectively transferred to the sinter mixture in a high-temperature zone and the temperature of the high-temperature zone is insufficient to answer the demand of the sintering mineralization consequently.…”
Section: Thermodynamic and Kinetic Conditions During Sinteringmentioning
confidence: 99%
“…Zhang et al [10] simulated the sintering process of iron ore by an unsteady two-dimensional mathematical model, which incorporated the significant physical phenomena and chemical reactions; sinter pot tests were also carried out. Wang et al [11] established a research route with sinter pot trials to characterize the evolution of the flame front and the phase chemistry along the bed height of sintering. Zhao et al [12] reported the evaluation model of iron ore properties based on the hightemperature characteristic numbers by employing fuzzy mathematics.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed the application of an algorithm based on the optimization of airflow rate as the control strategy for the sintering process. Wang et al [14] reported the evolution of the flame front and the mineral phases along the bed height of sintering.…”
Section: Introductionmentioning
confidence: 99%